The effect of an educational program according to the strategy of the cognitive load associated with some means of educational technology in teaching discus throwing effectiveness and retention (Journal of the College of Basic Education, 2022)
The aim of the research is to prepare an educational program with a strategy based on the theory of cognitive load and the owner of the program using educational means, including pictures and charts for the effectiveness of discus throwing. The researcher conducted the post tests, and through the results of the post tests, the researcher reached the effectiveness of the educational program and its success in teaching the skillful performance of discus throwing effectiveness and retention. And sports.